Pelaksanaan Penganalisisan Data Rekam Medis Elektronik (Studi Perancangan Sistem Informasi Analisis Kuantitatif) - Suyoko Suyoko; Faik Agiwahyuanto; Dyah Ernawati; Jaka Prasetya; Maulana Tomy Abiyasa (Politeknik Negeri Jember, 2024)
Telogorejo Hospital has implemented an electronic medical record (EMR) system. However, the documentation of EMRs remains incomplete, and completeness analysis is still conducted manually. This necessitates a quality improvement program within the digital transformation process to ensure complete EMR documentation. This study aims to investigate the implementation of EMR data analysis based on PMK 24 of 2022, as well as the design and evaluation of an information system for quantitative analysis of medical records. The research methodology employs a mixed-methods approach, combining Research and Development and descriptive research. The study was conducted in the medical record department from July to December 2023. Data collection methods include interviews, observations, and questionnaires. The system development utilizes the waterfall model, while testing employs the black box method and the TAM method for user acceptance evaluation. The findings indicate that the quality improvement program adheres to PMK 24 of 2022. However, doctors continue to use uncertified signatures for authentication, and mandatory settings for EMRs are absent. Application testing demonstrates successful operation, and TAM evaluation reveals that users strongly agree with the quantitative analysis application (90.5%). Recommendations include implementing certified electronic signatures and mandatory settings for EMR forms to optimize EMR completeness.